A Biocontainment Procedure for Intravital Microscopy of High-Risk Pathogens. (December 2018) - Haugh, Kelsey A.; Pi, Ruoxi; Fontes, Benjamin; Mothes, Walther; Uchil, Pradeep D.
Intravital multiphoton microscopy offers valuable spatio-temporal insight into studies of pathogen-host interactions. Although well established for studies with low-risk biohazard studies, the complexity of the intravital imaging technique has been difficult for applications using high-risk pathogens. Here, we delineate our standard operating procedure (SOP) for intravital microscopy studies of Risk Groups 2 and 3 pathogens. Using carefully designed protocols adapted to the pathogens under study, we present strategies that allow application of this complex technique to high-risk studies while maximizing protection of personnel and animals in the facility. While we describe our SOP for studies of HIV in vivo, these strategies serve as a guideline for designing SOPs for a wide variety of pathogen studies employing intravital imaging.